Bioactive profile of edible nasturtium and rose flowers during simulated gastrointestinal digestion - Bortolini, Débora Gonçalves (2022)
not widely explored. The gastrointestinal environment can modify these compounds, resulting in new combinations with different bioactivity. This study aimed to evaluate the effects of simulated gastrointestinal digestion (SGD) on rose and nasturtium flower extracts. Using UPLC-HRMS, 38 phenolic compounds were identified, and the SGD caused significant changes, mainly in the glycosylated phenolic. Furthermore, antioxidant activity was correlated with the increase in the concentrations of some polyphenols. Tested Gram-negative bacteria showed sensitivity to the flower extracts; their growth was inhibited by up to 82.7%. SGD interrupted the bacterial growth inhibition power of the rose extracts. On the other hand, an increase in inhibition ranging from 52.25 to 54.72% was found for nasturtium extracts, correlated to the behavior of some bioactive. Hence, SGD resulted in significant changes in phenolic profiles of the edible flowers, increasing antioxidant activity and changing antimicrobial effects.